PREVALENSI TINGKAT KECEMASAN REMAJA DI PANTI ASUHAN WISMA ANAK-ANAK HARAPAN DALUNG BALI TAHUN 2015 - Putu Suntiawati; Wayan Westa (Intisari Sains Medis, 2015)
Anxiety is a pathologic conditions that is characterized by fear and somatic symptoms which is the sign of hyperactivity of autonomic neuron. (Kaplan dan Saddock, 1997) Anxiety and fear have the same physiology components, but anxiety is different from fear. The etiology of anxiety comes from the inside and most of the source is unknown and fear is an emotional response for threat or danger which is from the outside that be faced consciously. (Maramis,2005) This study is a descriptive analytic that is a cross sectional study. The study take place in Wisma Anak-Anak Harapan Dalung orphanage. This study use a purposive random sampling. The sample was 30 teenagers in age 13-25 years old. Data obtained by interviewing the respondents one by one using HARS to know the anxiety’s level. The results obtained are the highest number in boys were found in medium anxiety which is 56,3%. The highest number for girls were found in light anxiety which is 57,1%. Besides that, data obtained there was 7,1% girls in very severe anxiety. Based on the age, data obtained was 33,3% from all of the respondents have light anxiety and 3,3% respondents have very severe anxiety. There were 46,2% respondents that had light anxiety was respondents in age 13-15 years old. Numbers 3,3% respondents that had very severe anxiety was respondents in age 16-20 years old.